(untitled) (Existential Analysis: Journal of the Society for Existential Analysis, 2002)
The present paper represents a phenomenological investigation into the ontological structure of revenge, through a reading of Edgar Allan Poe’s The Cask of Amontillado and Alexander Pushkin’s The Shot. It is proposed that revenge is a unique and paradoxical mode of being-in-the-world, whereby the avenger is consumed by a burning passion that combines psychological characteristics in paradoxical ways. It will be argued that what the avenger seeks is not retaliation, but a very particular outcome that reflects the original motive for revenge.